Está en la página 1de 4

 n (k(k + 2) + 2 k ) k=1 n (k − i) k=5 n (2k + 1) 2 k=1 n k=1 n 3 k + 2 k 5 k + 1 k 2 − k 2 + 2k + 1 1 1 k=1 n k=3 n 2 k 2 − 1 k 1 k=1 (2k − 1)(2k + 1)(2k + 3) n ( k 2 − 1 − k 2 + 4k + 3) k=10 n k=3 (k k + 1)! 20

i=1

50

i=10

n

k=1

n

k=1

(5

(i

3i 3 i )

2 i )

1

k(k + 1)

k

(k

+ 1)!

n

k=2

49

i=1

1

k 2 1

5 i+1

4 i

+ 2i 3i 2

1 + 11 + 111 + 1111 +

1 +

1

1

1

1 + 3 +
2

2

3

3 3

+

.

.

.

+

+ 11

1

1

3 10

(k + 1) 3 k 3 = 3k 2 + 3k + 1

70

7

k

k=1

120

(k 3)

k=4

250

k=15

k + 3 k + 5

2n

k=n 1

+ 2

2

k

60

k=1

n

k=1

n

k=2

20

k=1

3 k k

2

ln(4k)

k 2 1

k

2

2k1

j=k

2

j

n n

k=1

k=1

k 2 .

2 4 4 2

4

10 2

5

5

5 3

5

P OLO P AT AT A MISSISSIP P I

2 8 × 8 m × n

n

15 18 3 4

1

(0, 0) (3, 5)

(1, 2) (3, 4)

m < m n < n (m, n) (m, n‘)

k, p, n N 0 k p n

n

k

n

p

k

k

=

n

p

p

k

.

n

0

+ n + n

1

2

+

x 1 (1 + x) n 1 +

+ n

n

1

x n

x 11 (3x + 2x 2 ) 9

x 4 (1 + x)(1 x) n

x 5 (1 + x + x 2 ) 10

x 8 (1 + x x 2 ) 9

1 6 (12 + 3 · 2 2+n + 7n + 9n 2 + 2n 3 )

1 2 (5 + 2i n)(4 + n)

1 3 (11n + 12n 2 + 4n 3 )

1 6 (5 n (2 2+n 3 2+n + 13 · 5 n + 6 · 5 n n)

1

1

n 2 + 2n + 1 (n 2)(12n 2 + 17n + 3)

12n(1 n)

1

12

1

4(2n + 1)(2n + 3)

9 · 11 + 10 · 12 n(n + 2) (n + 1)(n + 3)

1 1

3! (n + 1)!

n

k=1

k 2 = n(n + 1)(2n + 1)

6

7 2485

197!

57

10795

2 + 4n 2 60 · 3 1830 · 60!

n

ln(4 n · n!) 1 + n

2n

2 1330